Unveiling the Intimate Mechanism of the Crocin Antioxidant Properties by Radiolytic Analysis and Molecular Simulations - Sarah Al Gharib; Pierre Archirel; Daniel Adjei; Jacqueline Belloni; Mehran Mostafavi (Antioxidants, 2023)
The successive steps of the oxidation mechanism of crocin, a major compound of saffron, by the free OH• radical are investigated by pulse radiolysis, steady-state (gamma) radiolysis methods, and molecular simulations. The optical absorption properties of the transient species and their reaction rate constants are determined. The absorption spectrum of the oxidized radical of crocin resulting from the H-abstraction presents a maximum of 678 nm and a band of 441 nm, almost as intense as that of crocin. The spectrum of the covalent dimer of this radical contains an intense band at 441 nm and a weaker band at 330 nm. The final oxidized crocin, issued from radical disproportionation, absorbs weaker with a maximum of 330 nm. The molecular simulation results suggest that the OH• radical is electrostatically attracted by the terminal sugar and is scavenged predominantly by the neighbor methyl site of the polyene chain as in a sugar-driven mechanism. Based on detailed experimental and theoretical investigations, the antioxidant properties of crocin are highlighted.